The Use of Mind Mapping on Economic Learning at SMK Negeri 1 Malang - Istiqomah, Ni’matul (Classroom Action Research Journal (CARJO), 2017)
Abstract The purpose of this research is to find out how mind mapping learning method can improve learning activeness in class. This research was conducted in SMK Negeri 1 Malang on Business Economics subjects material scarcity and sub theme of requirement. The sample in this research is students of class X AP 1 as many as 40 students. In the sample, the selection is not based on tribe, religion, race, and learning outcomes. In implementing the teaching, teachers apply 3 stages in accordance with the lesson plan that is the beginning, core, and closing activities. The application of mind mapping learning method is applied to the core stages of learning. The result of this research is student activeness in learning using mind mapping method looks increasing. Students are active and no students are found that are not active in learning. Keywords: Mind Mapping, Economic Learning, Classroom Research DOI: 10.17977/um013v1i12017p012